2017
DOI: 10.1159/000477907
|View full text |Cite
|
Sign up to set email alerts
|

Two Siblings with a Mutation in <b><i>CCDC8</i></b> Presenting with Mild Short Stature: A Case of 3-M Syndrome

Abstract: Background: Short stature can be caused by mutations in a multitude of different genes. 3-M syndrome is a rare growth disorder marked by severe pre- and postnatal growth retardation along with subtle dysmorphic features. There have only been 2 prior reports of mutations in CCDC8 causing 3-M syndrome. Methods: Two patients presenting with mild short stature underwent whole exome sequencing. The mutation was confirmed via Sanger sequencing. We compare the clinical characteristics of our 2 patients to patients pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is associated with reduced IGF2 expression and increased H19 expression, as also found in Silver-Russell syndrome (SRS). Characteristically, birth size is severely affected although individuals with milder intrauterine growth restriction have been reported ( 124 ).…”
Section: Clinical Management Of Children Born Sgamentioning
confidence: 99%
“…It is associated with reduced IGF2 expression and increased H19 expression, as also found in Silver-Russell syndrome (SRS). Characteristically, birth size is severely affected although individuals with milder intrauterine growth restriction have been reported ( 124 ).…”
Section: Clinical Management Of Children Born Sgamentioning
confidence: 99%
“…Another example is 3-M syndrome which is a rare syndromic growth disorder due to mutations in CUL7, OBSL1, or CCDC8 that usually presents with extreme short stature, skeletal dysplasia, and facial abnormalities. Interestingly, Liao L et al report 2 siblings with a previously reported pathogenic CCDC8 variant but only mild short stature (height −2.2 to −2.7 SDS) and subtle facial abnormalities [35].…”
Section: Mutations In Bmpr1b Gdf5mentioning
confidence: 99%